Nature of Nitrogen Incorporation in BiVO4 Photoanodes through Chemical and Physical Methods. Issue 1 (1st October 2019) - Irani, Rowshanak; Ahmet, Ibbi Y.; Jang, Ji-Wook; Berglund, Sean P.; Plate, Paul; Höhn, Christian; Böttger, Roman; Schmitt, Sebastian W.; Dubourdieu, Catherine; Lardhi, Sheikha; Cavallo, Luigi; Harb, Moussab; et al.
Abstract : In recent years, BiVO4 has been optimized as a photoanode material to produce photocurrent densities close to its theoretical maximum under AM1.5 solar illumination. Its performance is, therefore, limited by its 2.4 eV bandgap. Herein, nitrogen is incorporated into BiVO4 to shift the valence band position to higher energies and thereby decreases the bandgap. Two different approaches are investigated: modification of the precursors for the spray pyrolysis recipe and post‐deposition nitrogen ion implantation. Both methods result in a slight red shift of the BiVO4 bandgap and optical absorption onset. Although previous reports on N‐modified BiVO4 assumed individual nitrogen atoms to substitute for oxygen, X‐ray photoelectron spectroscopy on the samples reveals the presence of molecular nitrogen (i.e., N2 ). Density functional theory calculations confirm the thermodynamic stability of the incorporation and reveal that N2 coordinates to two vanadium atoms in a bridging configuration. Unfortunately, nitrogen incorporation also results in the formation of a localized state of ≈0.1 eV below the conduction band minimum of BiVO4, which suppresses the photoactivity at longer wavelengths. These findings provide important new insights on the nature of nitrogen incorporation into BiVO4 and illustrate the need to find alternative lower‐bandgap absorber materials for photoelectrochemical energy conversion applications. Abstract : Nitrogen is incorporated in BiVO4 by modifying the spray precursor solution (chemical) and through nitrogen ion implantation (physical). Both approaches lead to a slight decrease in the bandgap, but no extension of photoactivity. This observation is explained and the presence of molecular nitrogen (i.e., N2 ) in BiVO4 using X‐ray photoelectron spectroscopy and density functional theory calculation is revealed.